PENERAPAN MODEL PEMBELAJARAN NHT DENGAN PENDEKATAN SETS PADA MATERI CAHAYA UNTUK MENGEMBANGKAN KREATIVITAS SISWA (UPEJ Unnes Physics Education Journal, 2013)
The aim of this research was to find out the development of student creativities after the NHT learning model applied using SETS approach. The method used in this research was class action research. This research was done in SMP Negeri 3 Pemalang. The subjects of this research are 38 students of class VIII E in the academic year 2011/2012. Data obtained through the questionnaire students creativity. Students cognitive learning outcomes data obtained through evaluation tests in the form of multiple choice questions and a description. Psychomotor learning results obtained through observation sheet. The development of creativity and learning achievement done by gain test analysis. Based on these results it can be concluded that the application of learning NHT with SETS approach model can develop creativity and learning achievement.